The Impact of Board of Directors Effectiveness and Ownership Structure on Reducing Earnings Management - Haifawi, Bilal Mahmoud; Alrabba, Hussein Mohammed; Bataineh, Hanady Turki; Kanakriyah, Raed Mohammad (Jordan Journal of Business Administration, 2022)
This study aimed to examine the impact of board of directors effectiveness and ownership structure on reducing earnings management practices in the Jordanian manufacturing and service companies listed in Amman Stock Exchange during the period (2014-2017). Board of directors effectiveness was measured by: board independence, board size, multiple directorships and board meetings. On the other hand, ownership structure was measured by: institutional ownership, foreign ownership and government ownership. The dependent variable )earnings management( was measured based on the absolute value of discretionary accruals according to the modified Jones model. Four control variables were employed in the study (firm size, financial leverage, book to market ratio and type of audit firm). The sample of this study consists of (87) manufacturing and service companies listed in Amman Stock Exchange during the period (2014- 2017). Multiple regression analysis using Stata, version 14 was conducted to achieve the objectives of the study. The results showed a statistically significant negative relationship of foreign ownership, board independence and type of audit firm with earnings management. In light of these results, the study recommended to work on the development of laws and legislations that attract foreign investment, because it limits earnings manipulation by enhancing the concept of corporate governance, as well as the need of companies to comply with the corporate governance instructions, especially those associated with the independence of the board of directors because of its important role in reducing earnings management.